Revisiting the effect of sabot on the incident signals of split-Hopkinson pressure bar. (July 2023) - Kumar, Devender; Ruan, D.; Khaderi, S.N.
Abstract: In typical split-Hopkinson pressure bar set-ups, the striker bar is propelled in a barrel of larger diameter. Teflon/brass sabots are used to concentrically-align the striker inside the barrel. The influence of the area mismatch between barrel and striker, length of the sabots and interface condition between sabot and striker are analyzed in detail using finite element simulations. We show that for a given geometry of the sabot, a frictionless interface does not alter the incident signals. In the presence of friction, the incident signals deviate from the classical trapezoidal shape. The magnitude of the deviation depends on the geometry of the sabot. As an alternative to the shrink/press fitted sabot, a stepped striker is used to eliminate some issues faced during the usage of the shrink/press-fitted sabot. The stepped striker has a non-uniform diameter such that at two locations its diameter is that of the barrel, and at other locations it has the same diameter as the incident bar. The influence of the geometry of the stepped striker on the distortion of the incident signal is investigated in detail using the method of characteristics. A parametric study is used to quantify this distortion for various geometric configurations of the stepped striker. Three striker geometries are chosen from these configurations to validate the parametric study using experiments. High strain rate characterization of SS304 is also carried using these strikers to illustrate the effect of the geometry of the stepped striker on the stress versus strain and strain rate versus strain response. Highlights: The effect of shrink-fitted sabots on the incident signals is investigated. The incident signals depends on geometry of the sabots and the interface conditions. A stepped striker is proposed as an alternative to conventional strikers. Parametric study is conducted and results are validated experimentally. Material characterization is performed using the proposed strikers.